A morte do ladrão de migalhas - tradução, comentários e notas do poema herói-cômico, a batracomiomaquia - a guerra de rãs e ratos - Santos, Antonio Ricardo Paixão dos (2022)
Parody is defined as an imitative and burlesque genre. Its origin possibly dates back to Greek antiquity, but it is difficult to identify its appearance and author(s). In this study, we will work with the Greek parody of the Batrachomyomachia, a work in 304 verses, attributed to a Pseudo-Homero (c. 2nd century BC), developing a commented translation into Brazilian Portuguese. We aim to investigate and discuss the options decided upon by the translator in his target text, ascertaining whether both it and the source text are close to or far from it; and, thus, to expose how much presence the translator exerts in his target language text (in the aspect of visibility). From a theoretical point of view, we will research some concepts of translation (for example, the conception of original text), drawing on theories such as those of Pym (2017), Arrojo (2007), Amorim (2005), Venuti (2019, 2021), Schleiermacher (2010), Mundt (2008), and Sobral (2008).